Distribution and infestation levels of Crypticerya multicicatrices Kondo and Unruh (Hemiptera: Monophlebidae) on San Andrés island - Kondo, Takumasa Kondo; Becerra, Clever Gustavo; Quintero, Edgar Mauricio; Manrique B., Marilyn Belline (‎‎Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2019)
The fluted scale Crypticerya multicicatrices (Hemiptera: Monophlebidae) is an invasive insect that became a major pest on the island of San Andrés. To generate control strategies for this insect, its distribution and infestation levels on palm species, fruit trees, leguminous trees and other plant species were determined during January 14–18, 2013. A total of 96 points were sampled in order to determine the distribution of the insect on the island. During the study, the fluted scale was found distributed throughout the island of San Andrés, including Haynes Cay and Johnny Cay. The palms were the plants with the highest levels of infestation, 70.8% had some degree of infestation (37.5% high infestation levels); followed by fruit trees which had 65.6% with some degree of infestation (30.2% high infestation levels); followed by leguminous trees which had 59.6% with some degree of infestation (13.5% high infestation levels) and finally “other hosts” which had 51.1% with some level of infestation (11.5% high infestation levels). This study is the first detailed mapping of C. multicicatrices on the island of San Andrés which will become the basis for future work on the population dynamics of the fluted scale and its distribution on the island.